Deconstructivism approach towards the future of Malaysia architecture designs / Alice Sabrina Ismail and Mohd Hanif Masridin - Ismail, Alice Sabrina; Masridin, Mohd Hanif (Universiti Teknologi MARA, Perak, 2022)
As a multi-racial, multi-ethnic, multi-religious and multi-cultural country, there is a need for an architectural approach to translating the style of appearance and design that can highlight the diverse identity in the Malaysian context. Deconstructivism, a global approach to architecture, is hypothesized as an alternative solution to this problem. Inspired by the ideology and philosophy of 'Deconstruction' by Jacques Derrida, Deconstructivism emphasizes the interpretation of diverse design connotations through different layers of reality. This paper aims to find a suitable design recommendation through the architectural approach of Deconstructivism in Malaysia by taking a deeper look at the thinking behind the architectural approach of Deconstructivism and the design elements within it. In line with the idea behind Derrida's 'Deconstruction' philosophy, this paper utilizes the interpretivism paradigm as the primary methodology in interpreting the design and style of case study constructions. Through the method of 'building description', an analysis will be performed on two selected case studies based upon the eight Deconstructivism criteria that had been determined. These determinants are - deconstructing traditional Architecture Discourse; Non-Centrality of Construction; Paradox; Free- Floating Signifier; Trace and Presentness; Iterability and difference; Superimposition of Layers; and Deconstructing Binary Opposition. The findings obtained from the observational analysis of the form making and spatial organization of the case study will be supported by the data gained from interviews and literature studies. The study's findings are analyzed using hermeneutic as research methodology, whereas 'coding' and layering for data analysis techniques identify the extent to which the Deconstructivism of the architectural approach is adapted to the selected case study in Malaysia. This is vital to produce design recommendations for future designers to apply the deconstructivism style in the Malaysian architectural landscape for a different sense of an approach to create incredibly forward-thinking projects in exchange for leading Malaysian architecture to an innovative future.